ANALISIS PEMAHAMAN KERAGAMAN SUKU BANGSA DI NEGERIKU MELALUI MEDIA PETA PADA SISWA KELAS IV SD NEGERI 14 TANJUNG BATU - Rianita; Murjainah; Maharani Oktavia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to analyze the level of understanding of ethnic diversity in my country through the media of maps in grade IV students at SD Negeri 14 Tanjung Batu. The main object or informant in this study was the teacher at SD Negeri 14 Tanjung Batu while the students were the key informants. The research method used in this study is a qualitative descriptive method. Data collection techniques include interviews, tests and documentation, while data analysis techniques include data reduction, data display, and conclusion drawing. The results of the research on understanding IPS, interpreting, exemplifying, classifying, drawing inferences, dissecting and explaining that it can be seen that in the very good category there are 12 students, in the good category there are 8 students and in the sufficient category there are 3 students so that the level of understanding of Social Sciences with an average value 78 is included in the good category. From the results of the data analysis above, it can be concluded that the level of understanding of the subject matter of ethnic diversity in my country through the media of maps in grade IV SD Negeri 14 Tanjung Batu is good.